Investigating the non-radially polarized component of terahertz wave emission during single-colour femtosecond laser filamentation in air. (17th September 2018) - Zhao, Jiayu; Gao, Hui; Li, Shichang; Liu, Chang; Chen, Yamin; Peng, Yan; Zhu, Yiming
Abstract: Recently, simultaneous emission of radially and non-radially polarized terahertz (THz) pulses during single-colour femtosecond laser filamentation has been reported. In this work, the latter radiation has been specifically investigated, instead of the well-studied THz radial polarization. Briefly, cut-back measurements have verified that the ellipticity of the generated THz pulse with non-radial polarization decreased (became more linearly polarized) with the increasing filament length. The underlying mechanism responsible for this phenomenon is the existence of a propagation effect of THz wave along the filament plasma channel. In this case, the resulted off-axis propagation of THz wave inside the plasma column played a dominant role on the generated non-radial THz polarization, rather than the expected on-axis THz birefringence induced by the high laser intensity. This discovery will greatly renew the understanding of THz emission from plasma sources.